LOADING OF STRUCTURAL ELEMENTS OF LARGE-SIZED ROTATING AGGREGATES DURING LONG-TERM OPERATION: НАВАНТАЖЕННЯ КОНСТРУКТИВНИХ ЕЛЕМЕНТІВ ВЕЛИКОГАБАРИТНИХ ОБЕРТОВИХ АГРЕГАТІВ ПІД ЧАС ТРИВАЛОЇ ЕКСПЛУАТАЦІЇ - Kychma, A. O.; Predko, R. Ya. (Academic journal Industrial Machine Building Civil Engineering, 2018)
Methods for determining the teeth total skew angle crown engagement considering errors from manufacturing and from mutual arragement of pinion and coronal wheel of an open gearing are implemented. On the basis of experimental data, the possible range of the total skew angle has been determined for different conditions under which large-sized rotating aggregates are operated.Algorithm and techniques of calculation operated for a long time rotating aggregates during transitive and steady-state regimes of electromechanical drive mechanism operation, non-uniformity of the turn angle of the coronal wheel were considered. Practical recommendations for design improvement of an open gearing and for a system of kinematic parameters adjustment of large-sized rotating aggregates drive mechanism are suggested.
Keywords: rotating aggregate; gear crown wheel and pinion; drive mechanism; skew angles of teeth; weared out involute profil